Rehabilitating the Stroke Collection - Grimmond, Mary; Carter, Sharna; Lewis, Suzanne (Evidence Based Library and Information Practice, 2006)
Objective - The aim of this project was to complete an analysis of monograph and audiovisual items held in the Central Coast Health Service (CCHS) Libraries and containing information relevant to the treatment of acute stroke. Acute stroke is treated by multidisciplinary teams of clinicians based at two hospitals within the CCHS. The adequacy of the library collection was measured by subject coverage and age. Methods - The methodology used consisted of three main steps: a literature review; design, administration, and analysis of a questionnaire to members of the CCHS Acute Stroke Team; and an analysis of the libraries’ collections. The research project utilised project management methodology and an evidence based librarianship framework. Results - The questionnaire revealed that electronic resources were by far the most frequently used by participants, followed in order by print journals, books, interlibrary loan articles, and audiovisual items. Collection analysis demonstrated that the monograph and audiovisual collections were adequate in both scope and currency to support the information needs of Acute Stroke Team members, with the exception of resources to support patient education. Conclusion - The researchers developed recommendations for future collection development in the area of acute stroke resources. Conducting this project within the evidence based librarianship framework helped to develop library staff members’ confidence in their ability to make future collection development decisions, informed by the target group’s information needs and preferences. The collection analysis methodology was designed to be replicated, and new specialist groups within the client base of the library will be targeted to repeat the collection analysis process.